2019
DOI: 10.1016/j.jtumed.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Common medical ethical issues faced by healthcare professionals in KSA

Abstract: ObjectiveThere are growing concerns about ethical issues in the healthcare system. This study was conducted to determine the nature of common ethical issues faced by healthcare providers in a tertiary-care hospital in KSA.MethodThis cross-sectional study comprised a self-administered questionnaire given to the physicians working at King Abdulaziz Medical City Hospital-Riyadh, Ministry of National Guard Health Affairs (KAMC-RD, MNGHA). We used a convenience sampling technique during symposia and conferences.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The conclusions and recommendations of all included articles were consistent, stating that teaching bioethics is a complex and long-term process that helps graduate and undergraduate students embrace the roots of their culture, knowledge, and principles [22][23][24][25][26][27][28][29][30][31]. While there is no single best model for teaching medical ethics, teaching bioethics is essential to educating medical students by developing a comprehensive bioethics curriculum.…”
Section: Medical Ethics Curriculummentioning
confidence: 98%
See 2 more Smart Citations
“…The conclusions and recommendations of all included articles were consistent, stating that teaching bioethics is a complex and long-term process that helps graduate and undergraduate students embrace the roots of their culture, knowledge, and principles [22][23][24][25][26][27][28][29][30][31]. While there is no single best model for teaching medical ethics, teaching bioethics is essential to educating medical students by developing a comprehensive bioethics curriculum.…”
Section: Medical Ethics Curriculummentioning
confidence: 98%
“…However, it would be fair to note that there is still limited guidance on teaching and learning bioethics, which will inevitably have a tangible impact on society in the future [1,2]. Despite the researchers' growing interest in medical ethics, this systematic review has shown that from 2010 to 2021, only ten articles were published studying the 'Medical Ethics Curriculum' in KSA [22][23][24][25][26][27][28][29][30][31]. Of these ten articles, the research by El-Sobkey et al ( 2014) is in the list of the most cited articles with 21 citations.…”
Section: Medical Ethics Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare professionals frequently encounter situations that involve medical ethical principles leading to ethical dilemmas [16,17]. In the past few decades, the use of courts, to resolve intractable ethical dilemmas, has increased across both developed and developing countries [18][19][20][21].…”
mentioning
confidence: 99%
“…The first solution to a lack of medical ethics' knowledge and reasoning is to improve scientific ethics teaching to health professionals in the curricula. However, a lack of trained medical ethics specialists,[ 22 ] a lack of enough medical ethics' teaching time in the curricula, and a lack of scientific approaches in teaching ethics to medical students lead to a lack of knowledge and skill required for ethical judgment among medical professionals. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%